2013
DOI: 10.1111/efp.12070
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence, incidence and associations among fungal pathogens and Agrilus auroguttatus, and their roles in Quercus agrifolia decline in California

Abstract: Synchronous decline of oak (Quercus spp.) trees in woodlands has been described in Europe and eastern North America as a complex interaction of stressors that predispose, incite or contribute to tree death. This study presents a 2-year (2010-2011) assessment of the role of pathogens in coast live oak (Quercus agrifolia) woodlands in southern California where oak mortality occurs in locations that are infested and uninfested by the goldspotted oak borer (GSOB, Agrilus auroguttatus). Cumulative coast live oak mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…However, Haavik et al 13 also reported generally low rates of appearance of symptoms of A. auroguttatus infestation (emergence hole density, woodpecker activity and bark staining), as well as tree mortality (5 out of 722 trees), at six survey sites on the periphery of the zone of infestation in San Diego County. Lynch et al 41 also reported low levels of oak mortality in the same general area. In some instances, crown dieback rating decreased during the survey period (Tables 1 and 2).…”
Section: Emergence Hole Density and Rate Of A Auroguttatus Infestatimentioning
confidence: 84%
“…However, Haavik et al 13 also reported generally low rates of appearance of symptoms of A. auroguttatus infestation (emergence hole density, woodpecker activity and bark staining), as well as tree mortality (5 out of 722 trees), at six survey sites on the periphery of the zone of infestation in San Diego County. Lynch et al 41 also reported low levels of oak mortality in the same general area. In some instances, crown dieback rating decreased during the survey period (Tables 1 and 2).…”
Section: Emergence Hole Density and Rate Of A Auroguttatus Infestatimentioning
confidence: 84%
“…Earlier reports of D. corticola in North America (including identification of strains to which other names had been applied) document presence within the extreme eastern, southern and western United States (Figure a). These include Maine (Aćimović et al., ), Massachusetts (Munck et al., ), Pennsylvania (Martin & Munck, ), Washington, D.C. (Alves et al., ; Jacobs & Rehner, ), West Virginia (Martin et al., ), North Carolina (Alves et al., ), Florida (Dreaden et al., ), Texas (Úrbez‐Torres et al., ) and California (Alves et al., ; Jacobs & Rehner, ; Lynch et al., ; McPherson et al., ; Úrbez‐Torres et al., ) (Figure a). Some of these reports describe occurrence of the pathogen at only a single location and/or point in time.…”
Section: Discussionmentioning
confidence: 99%
“…Lynch et al. () examined 857 coast live oak trees in two California counties in which large‐scale oak die‐off occurred. Diplodia corticola was one of the three most frequently cultured fungi considered “aggressive” pathogens in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations